The space diversity analysis of bidirectional antenna using probe excited circular ring - Maruekin, Manoon; Phongcharoenpanich, Chuwong; Kosulvit, Sompol (My University, 2004)
This paper presents a space diversity analysis of bidirectional antenna using probe excited circular ring. The theoretical investigation is first carried out. The operating frequency is performed at 1.9065GHz. The electromagnetic fields of the ring with the aperture directs in z-axis is first calculated. Then, the transformations to x direction is achieved. The diversity characteristics such as mean effective gain correlation coefficient, and diversity gain are determined and compared among the arrangement in x,y and z directions.
Keywords: Bidirectional antenna; Space diversity